Advanced strategies to evade the mononuclear phagocyte system clearance of nanomaterials. Issue 1 (5th January 2023) - Lu, Junjie; Gao, Xiao; Wang, Siyao; He, Yuan; Ma, Xiaowei; Zhang, Tingbin; Liu, Xiaoli
Abstract: Nanomaterials are promising carriers to improve the bioavailability and therapeutic efficiency of drugs by providing preferential drug accumulation at their sites of action, but their delivery efficacy is severely limited by a series of biological barriers, especially the mononuclear phagocytic system (MPS)—the first and major barrier encountered by systemically administered nanomaterials. Herein, the current strategies for evading the MPS clearance of nanomaterials are summarized. First, engineering nanomaterials methods including surface modification, cell hitchhiking, and physiological environment modulation to reduce the MPS clearance are explored. Second, MPS disabling methods including MPS blockade, suppression of macrophage phagocytosis, and macrophages depletion are examined. Last, challenges and opportunities in this field are further discussed. Abstract : Mphagocyticononuclear system (MPS) is one of the major obstacles that impede the accumulation of nanomaterials at their target sites. This Review summarizes the advanced strategies for evading the MPS clearance of nanomaterials, and discusses the challenges and opportunities in this field.